The relation of echo‐derived lateral MAPSE to left heart functions and biochemical markers in patients with preserved ejection fraction: Short‐term prognostic implications. Issue 5 (8th March 2022) - Ozer, Pelin Karaca; Govdeli, Elif Ayduk; Demirtakan, Zeynep Gizem; Nalbant, Aslı; Baykiz, Derya; Orta, Huseyin; Bayraktar, Berk Batuhan; Baskan, Serra; Umman, Berrin; Bugra, Zehra
Abstract: Objective: Mitral annular plane systolic excursion (MAPSE) is a simple way to evaluate—left ventricle (LV) function. Our aim was to explain the relationship of MAPSE with LV function and biochemical markers in patients with preserved ejection fraction (EF), and to determine whether it has an effect on prognosis in echocardiography (echo) practice. Methods: Consecutive patients referred to the echo laboratory between November 2020 and March 2021 were included in the study. In addition to conventional parameters, MAPSE of the lateral mitral annulus was measured in all patients. Patients were divided into three groups according to lateral MAPSE: low (<12 mm), relatively preserved (12–15 mm), and high (≥15 mm). Results: A total of 512 patients with preserved EF were included in the study. MAPSE was low in 44 patients (9%), relatively preserved in 231 patients (45%), and high in 237 patients (46%). The mean age was higher in the low group compared to the other two groups ( p  < 0.001) and the body mass index was increased in the low group compared to the high group ( p  = 0.010). Atrial fibrillation and hypertension were more common in patients with low MAPSE. The rate of diastolic dysfunction (DD) and all‐cause hospitalization were higher in the low and relatively preserved groups than in the high group ( p  < 0.001, p  = 0.002; respectively). The pro‐BNP level and mortality rate were higher in the low group compared to the relatively preserved and high groups ( p  = 0.007, p  = 0.005; respectively). MAPSE was identified as independent predictor of hospitalization (OR: 0.284, 95% CI: 0.093–0.862, p  = 0.026) via multivariate analysis and independent predictor of in‐hospital mortality (HR: 0.002, 95% CI: 0–0.207, p  = 0.008). Conclusions: Analysis of LV longitudinal function by echo‐derived lateral MAPSE when LV ejection fraction is normal provides important information about DD and related heart failure and may predict prognosis in echo practice. Abstract : In this study, the relation of lateral mitral annular plane systolic excursion (MAPSE) measured by echocardiography in routine practice with clinical and laboratoray parameters, diastolic dysfunction, heart failure, and prognosis was demonstrated in patients with preserved LV ejection fraction.